The Effect of Gargling Young Coconut Water (Cocos Nucifera L.) On Changes In Salivary pH In Children At SMP Negeri 1 Muara Pinang, Empat Lawang - Shafira Ari Yuni; Abu Hamid (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. Dental caries is one of the various dental health cases that has a high prevalence in Indonesia. One of the variables that influences the development of dental caries is saliva. The way to control the acidity (pH) of saliva is to gargle with antibacterial fluid. Young coconut water (Cocos Nucifera L.) contains tannins or antidote (anti-toxic). The aim is to determine the effect of gargling young coconut water (Cocos Nucifera L.) on changes in the pH of saliva. Methods. This research uses a quasi-experimental research type with a pre-test post-test design and a control group (comparison group) using a purposive sampling technique. Results. Proves that there is a significant impact on the pH of saliva before and after gargling with young coconut water, namely before gargling the pH is 7.645 and after gargling the pH is 7.325 or it can be concluded that there is an effect of consuming coconut water on changes in saliva pH. Conclusion. There is a significant effect of gargling young coconut water (Cocos Nucifera L.) on saliva pH.